The function of DIS3L2 in the mechanism of nonsense-mediated mRNA decay - Garcia-Moreno, Juan (2019)
In the flow of information from DNA to mRNA to proteins, mRNAs undergo a number of processing steps, since they are synthesized in the nucleus, until they are translated in the cytoplasm. Eukaryotic cells tightly control the fidelity of this process, via quality control pathways, among them, the nonsense-mediated mRNA decay (NMD). NMD recognizes and degrades mRNAs harboring premature translation-termination codons (PTCs), protecting the cell from potentially harmful truncated proteins. However, NMD can also regulate normal and fully functional mRNA levels, arising as a surveillance and a gene expression regulation pathway. A new branch of the NMD pathway is starting to be revealed, which is characterized by the involvement of the DIS3L2 3’ to 5’ exoribonuclease. This protein has special relevance, given its exosome-independent action and its uridylation-mediated decay. In addition, mutations on this ribonuclease induce deregulation of cell-cycle genes leading to a faster cell growth and decreased chromosome stability, while DIS3L2 downregulation enhances cancer stem cell properties. Several lines of evidence point to an oncogenic role of DIS3L2 and its mediated decay over a number of NMD targets, however further research is needed to unveil the mechanism by which this nuclease is involved in NMD and how it mediates cancer related processes. In this work, we show the DIS3L2 involvement in the NMD target regulation, by its dependent action on the NMD central player, UPF1. We also aim to analyze how DIS3L2 and uridylation regulate the human transcriptome, in order to shed light on how this ribonuclease is related to NMD and how its deregulation contributes to tumorigenesis. For this purpose, high-throughput mRNA sequencing has been performed in the SW480 colorectal cancer cell line depleted of DIS3L2 or DIS3L2 plus terminal uridylyl transferases (TUTases), TUT4 and TUT7.